LIS-based Inspection Knowledge Graph Construction System - Fu, Fengyang; Sun, Shuangling; Liu, Yi (Transactions on Computer Science and Intelligent Systems Research, 2023)
In order to fill the lack of knowledge graph based on real experimental data from Laboratory Information System (LIS) in the field of medical testing, a method and system for constructing medical testing knowledge graph based on LIS is proposed. The problem of how to obtain rich and accurate literature resources of medical specialty from the real world is solved by building a database and tools such as reasoning machine. Using a large number of clinical laboratory specimens as a data source, data mining technology is used to analyze and process the massive information, so as to generate a high-quality visualization of the medical test knowledge graph. Doctors first do some pre-diagnostic preparations for patients, and then conduct a comprehensive and systematic physical examination. By building a medical test knowledge map, we have brought new possibilities for the application scenarios of LIS system.